2002
DOI: 10.1136/jcp.55.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori associated gastric diseases and lymphoid tissue hyperplasia in gastric antral mucosa

Abstract: Aim: To investigate the relation between Helicobacter pylori associated gastroduodenal diseases and lymphoid tissue hyperplasia in the antral mucosa and to pursue its evolution after eradication of H pylori. Methods: Gastric antral biopsy specimens were obtained from 438 patients with H pylori positive gastroduodenal diseases (185 chronic gastritis, 69 gastric ulcer, and 184 duodenal ulcer) and 50 H pylori negative healthy controls. Lymphoid follicles and aggregates were counted and other pathological features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
5
42
0
9
Order By: Relevance
“…A higher incidence was seen in males with an M : F ratio of 2.1 : 1. Chen et al [7] also found a M : F ratio of 1.8 : 1.…”
Section: Discussionmentioning
confidence: 92%
“…A higher incidence was seen in males with an M : F ratio of 2.1 : 1. Chen et al [7] also found a M : F ratio of 1.8 : 1.…”
Section: Discussionmentioning
confidence: 92%
“…Nishijima et al [39] Nagano et al [40] 47 F 1 1.7 RLH Chronic thyroiditis, high titer of ANA 16 Pantanowitz et al [41] 69 F 2 1.7, 1.0 RLH Renal cell carcinoma 17 Okubo et al [2] 49 F 1 2 PL Sjögren's syndrome 18 Mori et al [42] 49…”
Section: Discussionmentioning
confidence: 99%
“…In other organs, several factors are thought to be associated with pseudolymphoma, i.e. EpsteinBarr virus (hard palate and oral mucosa [14] ), mechanical stimulation (ear [15] ), anticonvulsant drugs (skin [16] ) and Helicobacter pylori (H pylori) (stomach [17,18] ). Regarding the association of H pylori with gastric pseudolymphoma, successful treatment of the pseudolymphoma by eradication of H pylori has been reported [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DGM has been observed in 13% to 42% of children infected with Hp [5][6][7], however, there is no definitive correlation between the influence of chronic duodenitis and duodenal ulceration with the presence DGM [8]. DGM is common in the proximal duodenum and in persons over 7 years of age [9][10][11]. Duodenal ulcer prevalence increases with age, and its higher incidence is related with the chronic gastritis associated with Hp infection.…”
Section: Introductionmentioning
confidence: 99%
“…Because the prevalence of non-specific vs. Hp gastritis of cases reviewed at the service is approximately 3:1, 70 biopsy specimens with Hp infection (cases) and 220 with non-specific gastritis (controls) were included, although in the literature it has been reported to be 5:1 [8,10].…”
Section: Methodsmentioning
confidence: 99%